2014
DOI: 10.1002/mrm.25318
|View full text |Cite
|
Sign up to set email alerts
|

Interleaved diffusion-weighted improved by adaptive partial-Fourier and multiband multiplexed sensitivity-encoding reconstruction

Abstract: Purpose We report a series of techniques to reliably eliminate artifacts in interleaved echo-planar imaging (EPI) based diffusion weighted imaging (DWI). Methods First, we integrate the previously reported multiplexed sensitivity encoding (MUSE) algorithm with a new adaptive Homodyne partial-Fourier reconstruction algorithm, so that images reconstructed from interleaved partial-Fourier DWI data are free from artifacts even in the presence of either a) motion-induced k-space energy peak displacement, or b) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 26 publications
0
57
0
Order By: Relevance
“…As shown in recent papers, 2D MUSE was designed to estimate shot-to-shot phase variations directly from interleaved EPI data without relying on navigator echoes (Chang et al, 2014; Chen et al, 2013; Chu et al, 2014). However, for 3D interleaved EPI, navigator signals with zero k z encoding are needed (Figure 1), because the shot-to-shot phase variations cannot be inherently estimated from weak DWI signals at high k z planes.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in recent papers, 2D MUSE was designed to estimate shot-to-shot phase variations directly from interleaved EPI data without relying on navigator echoes (Chang et al, 2014; Chen et al, 2013; Chu et al, 2014). However, for 3D interleaved EPI, navigator signals with zero k z encoding are needed (Figure 1), because the shot-to-shot phase variations cannot be inherently estimated from weak DWI signals at high k z planes.…”
Section: Discussionmentioning
confidence: 99%
“…MR-gRT solutions are being made rapidly to overcome the obstacles associated with MR-only workflows encompassing QA devices, novel dose calculation algorithms that can account for magnetic field dose perturbances, fast automated contouring algorithms and imaging protocols for intrafraction motion monitoring and plan adaptation. 61,77,84,85 Another potential solution to the issue of cost-effectiveness of this technology would be to determine if the addition of off-line MRI simulations might improve the accuracy of current day IGRT while improving patient throughput on MR-gRT systems.…”
Section: Resultsmentioning
confidence: 99%
“…It is to be noted that recent developments such as multiplexed sensitivity encoding and simultaneous multislice potentially provide sufficient spatial resolution to be used for real-time image guidance. 61,62 The ability of magnetic spectroscopy imaging (MRS) to diagnose areas of high metabolic activity linked to tumour cell proliferation is particularly useful for RT treatment planning because of better gross tumour volume delineation. 27 MRS can also help during image guidance by daily tumour imaging facilitating simultaneous integrated boost treatments.…”
Section: Biomarkers and Mrimentioning
confidence: 99%
“…Recently, alternating methods applying PI techniques were introduced. 4, 16,17 In, 4 author showed that when the number of shots is between 2 to 4, GRAPPA is superior to SENSE in the sense of immunity to motion while SENSE has slightly higher SNR. In 16 and, 17 author introduced a reconstruction scheme for MS-EPI based on SENSE.…”
Section: Introductionmentioning
confidence: 97%